Strategy for Achieving Social Performance of the Kanindo Syariah Cooperative, Dau Malang Branch - Abdillah, Muqaffi; Manzilati, Asfi; Noor, Iswan (AIBPM Publisher, 2023)
For sharia financial institutions that runs their business based on the philosophy of the Qur'an and Sunnah, social performance is the basis for actors in interacting with the environment and each other. One method of reporting social performance for sharia companies is the Islamic Social Reporting Index method (ISR). However, this method is still considered inappropriate to be applied to sharia financial institutions, which requires sharia financial institutions to develop their own social strategies. This research aims to determine the strategy for achieving social performance in the Dau branch of the Kanindo Syariah cooperative and to dig deeper into the reasons why the ISR method is not suitable for application to Sharia Financial Institutions. This research uses descriptive qualitative research methods. The results of the research shows that Kanindo Syariah Dau branch has a strategy consisting of collecting and dsitributing social funds internally and externally. As for the ISR method, three conclusions were obtained which are the reasons why this method is not appropriate for sharia financial institutions, (1) lack of concern for the environment, (2) lack of understanding regarding maqashid sharia, and (3) lack of suitability for the environmental theme of the institutions which operates in the financial sector. Keywords: Strategy, Social performance, Islamic Social Reporting Index, Sharia Financial Institutions, Environment.